2017
DOI: 10.1002/prca.201600163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extracellular matrix protein 1 as a potential plasma biomarker of ESCC by proteomic analysis using iTRAQ and 2D‐LC‐MS/MS

Abstract: This proteome analysis indicate that ECM1 is a potential novel plasma protein biomarker for the detection of primary ESCC and evaluation of neoplasms progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Moreover, it is involved in various biological processes, such as cell proliferation, angiogenesis, migration and metastasis 11,12. ECM1 was found to promote metastatic progression and invasion in multiple cancer types, and overexpression of ECM1 has been incorporated into scoring models for indicating of poor clinical prognosis and metastatic potential in cancer patients 13,14. Compared with non-lymph node metastases, breast and lung tumors with lymph node metastases were more likely to be ECM1-positive 15.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is involved in various biological processes, such as cell proliferation, angiogenesis, migration and metastasis 11,12. ECM1 was found to promote metastatic progression and invasion in multiple cancer types, and overexpression of ECM1 has been incorporated into scoring models for indicating of poor clinical prognosis and metastatic potential in cancer patients 13,14. Compared with non-lymph node metastases, breast and lung tumors with lymph node metastases were more likely to be ECM1-positive 15.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high ECM1 level in serum of BC patients is associated with recurrence of tumor [156]. ECM1 is a potential plasma protein biomarker for the detection and progression of primary ESCC [157]. It is an unfavorable prognostic marker in renal cancer, urothelial cancer, and PDAC [36].…”
Section: Extracellular Matrix Protein I (Ecm1_human)mentioning
confidence: 99%
“…Strong positive lumican immunostaining was found in the stromal and epithelial compartments of ESCC specimens but was almost negative in normal epithelium[ 103 ]. The concentration of lumican in plasma was identified as a potential biomarker of ESCC via a proteomic screen[ 104 ]. Nevertheless, a previous study by our group comparing a highly invasive ESCC subline with its parental cells showed that LUM decreased 8-fold in the highly invasive subline and was accompanied by activation of AKT pathway[ 105 ].…”
Section: Extracellular Proteoglycans In Esccmentioning
confidence: 99%